Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1155/2019/5820415
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine Attenuates the Endotheliotoxicity and the Mitochondrial Dysfunction by Doxorubicin via 14-3-3γ/Bcl-2

Abstract: Doxorubicin (Dox) with cardiotoxicity and endotheliotoxicity limits its clinical application for cancer. The toxicitic mechanism involves excess ROS generation. 14-3-3s have the protective effects on various injured tissues and cells. Tetramethylpyrazine (TMP) is an alkaloid extracted from the rhizome of Ligusticum wallichii and has multiple bioactivities. We hypothesize that TMP has the protective effects on vascular endothelium by upregulating 14-3-3γ. To test the hypothesis, Dox-induced endotheliotoxicity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 69 publications
1
21
0
1
Order By: Relevance
“…14-3-3 is the molecular target of many active ingredients of plants. We have confirmed that 14-3-3 assists PKCε, Bcl-2, and other functional proteins to locate to mitochondria and protect cardiomyocytes and vascular endothelial cells against multiple injuries [7,9,[40][41][42][43]. Further studies are needed to define specific mechanism(s) of action for Cap-activated 14-3-3η in anoxia and A/R injured cardiomyocytes.…”
Section: Discussionsupporting
confidence: 53%
“…14-3-3 is the molecular target of many active ingredients of plants. We have confirmed that 14-3-3 assists PKCε, Bcl-2, and other functional proteins to locate to mitochondria and protect cardiomyocytes and vascular endothelial cells against multiple injuries [7,9,[40][41][42][43]. Further studies are needed to define specific mechanism(s) of action for Cap-activated 14-3-3η in anoxia and A/R injured cardiomyocytes.…”
Section: Discussionsupporting
confidence: 53%
“…TMP is a promising candidate for managing cardiovascular and cerebrovascular diseases [10][11][12]. Our previous study also articulated that TMP has excellent protective function on a variety of the myocardium and blood vessel injuries [13][14][15][16]. In this study, we characterized the effect of vinegar/TMP pretreatment in alleviating A/R-induced myocardial damage by multiple functional, enzymatic, cellular, or molecular biological indicators (Figures 2-5, Table 2).…”
Section: Discussionmentioning
confidence: 96%
“…Previously, we have found that TMP has an excellent protection on a variety of the myocardium or blood vessel injuries [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that targeted cancer therapies, such as doxorubicin [ 15 ], anthracycline [ 16 ], and cantharidin [ 17 ], can result in cardiovascular toxicities. The adverse effects of chemotherapy drugs may result from impaired mitochondrial function, increased oxidative stress [ 15 , 18 ], increased mitochondria-proteasome interactions [ 19 ], impaired mitochondrial autophagy [ 20 , 21 ], activation of mitochondrial inflammation signaling pathways such as NF- κ B [ 22 ], mitochondrial energy metabolic dysfunction [ 23 ], and mitochondrial apoptosis [ 24 ]. In addition, ER-mediated abnormalities in intracellular calcium signaling, protein misfolding as a result of ER stress, and ER-dependent cell apoptosis [ 25 27 ] can also contribute to cardiomyocyte damage during chemotherapy.…”
Section: Introductionmentioning
confidence: 99%